An energy efficient clustering scheme using multilevel routing for wireless sensor network. (July 2018) - K, Muthukumaran; K, Chitra; C, Selvakumar
Abstract: The wireless sensor network (WSN) has attracted much research interest due to its many potential applications in different fields. In this work, we have tried to improve energy efficiency at the node level and to increase the network lifetime by proposing routing model called energy-efficient clustering (ENEFC) based on a hierarchical routing scheme. The proposed ENEFC provides three different hierarchical routing schemes: hierarchical routing using cluster identification (HRCI), hierarchical routing using multi-hop (HRMH) and hierarchical routing using multilevel (HRML). The HRML assigns a level to each cluster head during the publicizing of the base station over the entire network, and when the route collapses the scheme efficiently establishes a new level for the route between the base station and cluster heads. The experimental results and analyses for the three schemes show that HRML is more effective in terms of energy efficiency than the other two schemes.